The Archaeology of the Digital Periphery: Computer Mice and the Archaeology of the Early Digital Era. (17th January 2019) - Beale, Gareth; Schofield, John; Austin, Jim
Abstract : The computer mouse is one of the most familiar artefacts of the developed world to have been devised in the late twentieth century. The essential form remains the same as when it was first invented, but during this time the mouse has transformed our physical interaction with and perception of computers. With increased attention being paid to curating and collecting technologies of the contemporary world, and within the context of an archaeological research culture that extends to the contemporary, an archaeological examination of this ubiquitous object appeared timely. There are millions - if not billions - of mice in circulation, including models that are now outdated or obsolete. Despite their apparent uniformity they differ in significant ways, and examination of these differences can help us to understand human experiences of technology in ways that resonate with artefact types of much earlier periods. With that time depth in mind, this paper will therefore focus on the form and function of the computer mouse and its place in the contemporary imagination. This will be followed by a detailed study of five specific examples which together illustrate some of the key issues and challenges that face us, as archaeologists and curators.